Compensador série de tensão em onda quadrada com retificador controlado por seleção de taps do transformador shunt - Marcos Paulo Brito Gomes (2019)
Electric power quality (PQ) is a worldwide concern for consumers and electric utilities that aims to investigate related phenomena and meet standards that ensure the compliance of power systems. Voltage sag, according to the American scientific community, or voltage dips according to the European community, fit into the groups of higher severe power quality phenomena, implying losses for the most varied productive segments. Series Voltage Compensators (SVC) or Dynamic Voltage Restorers (DVRs) have become effective solutions for mitigating voltage sags and voltage swell, based on Power Electronics with several efficient topologies. The evolution of SVCs is in order to improve the cost-benefit of equipment, reduction of energy storage components, filters, coupling transformers with the network as well as the simplification of control and synchronism. This work presents a study of SVCs with equally simplified topologies that are capable to maintaining voltage in susceptible loads. It is estimated that the problems of power quality generate productive losses and stops in the manufacturing process at industries, because of sensitive loads to voltage variation and problems from the power grid, such as voltage sag. First, the conventional sinusoidal SVC will be introduced, and then three simplified topologies will be discussed with the proposal of Square Wave Series Voltage Compensators (SW-SVC), capable to compensating voltage sags and swells with better cost-benefit ratio. Simulations and experimental results of simplified SW-SVC will be presented. The design includes a description of the inherent systems parts, such as the coupling transformer, harmonic filter at the output of the static power converter, topology, configuration and its semiconductors, input rectifier, and grid synchronization system. Next, will be discussed the compensator performance acting during voltage sag, improving the susceptibility of local electronic loads at low voltage level known as low voltage ride through capability (LVRT).